Nematic fluid at a hard wall in the mean field approximation - Holovko, M.; Kravtsiv, I.; di Caprio, D. (Condensed Matter Physics, 2013)
In the framework of a field theoretical approach we study Maier-Saupe nematogenic fluid in contact with a hard wall. The pair interaction potential of the considered model consists of an isotropic and an anisotropic Yukawa terms. In the mean field approximation the contact theorem is proved. For the case when the nematic director is oriented perpendicular to the wall, analytical expressions for the density and order parameter profiles are obtained. It is shown that in a certain thermodynamic region the nematic fluid near the interface can be more diluted and less orientationally ordered than in the bulk region. В рамках теоретико-польового пiдходу вивчається нематогенний плин Майєра-Заупе бiля твердої поверхнi. У розглядуванiй моделi парний потенцiал взаємодiї складається з iзотропного та анiзотропного Юкавiвських доданкiв. У наближеннi середнього поля доведено контактно теорему. Для випадку, коли директор направлений перпендикулярно до стiнки, отримано аналiтичнi вирази для профiлiв густини та параметра порядку. Показано, що у певнiй термодинамiчнiй областi нематичний плин поблизу поверхнi може бути бiльш розрiдженим i менш орiєнтацiйно впорядкованим, нiж в об’ємнiй областi.